Simulations on the rheology of dry magneto-rheological fluid under various working modes. (6th December 2021) - Pei, Lei; Ma, Zongqiang; Ma, Dongjun; Shi, Xiaofeng; Pan, Hao; Wang, Pei; Gong, Xinglong
Abstract: This work studied the rheological properties and magnetorheological (MR) mechanism of dry magnetorheological fluid (MRF) under various working modes. A novel simulation method combining the discrete element method and computational fluid dynamics was developed, in which the bilateral coupling between particles and the flow field of the matrix (air) was considered. The microstructures and mechanical properties in the redispersion process, shear mode, and valve mode were systematically simulated for the first time. The results indicated that dry MRF presented superior redispersion property and response time (several μ s) than liquid-based MRFs. In shear mode, the magnetic dipolar force and friction force dominated the evolution of microstructures. In valve mode, the magnetic dipolar force and viscous drag force of air became the main interactions. Magnetic particles aggregated into sturdy chain structures and hindered the airflow. The MR effect in valve mode was the pressure gradient of the matrix, which increased up to 1.08 × 10 5 Pa m −1 with the increasing particle volume fractions and decreased under a large inflow velocity. The best MR effect in valve mode was achieved under a magnetic field of B = 63 mT. Simulations revealed the influence of dimensionless Mn and Re number on the MR effect. The pressure gradient of the matrix was controlled by the external field and can be utilized to design a dry MRF valve for precious and transient vibration control. Simulated dimensionless shear stress in shear mode agreed well with experiments. This work will promote the development and applications of novel high-performance MRFs.